10.6k views
2 votes
Simplify (3x + 2)(4x - 4)

1 Answer

1 vote

Answer:

12x² - 4x - 8

Explanation:

Use FOIL method

(3x + 2)(4x - 4) = 3x*4x + 3x*(-4) + 2 *4x + 2*(-4)

= 12x² - 12x + 8x - 8 {add like terms}

= 12x² - 4x - 8

Hint: 3x * 4x -----> Multiply the coefficients = 3 *4 = 12 and then multiply the variables and for multiplying the two variable, add the powers

x*x =
x^{1+1)=x^(2)

3x * 4x = 12x²

User Tinny
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.